Pathways and consequences of legal irregularity : senegalese migrants in France, Italy and Spain (2019)
Irregular migration has become a politically controversial issue in most immigrantreceiving countries. Academic research has shown that states and their immigration policies actively create the legal conditions for the existence and perpetuation of irregular migration. Much of this literature, however, focuses on the United States and thus cannot examine how variation in contexts of reception may produce different configurations of legal status. In addition, much research on immigration has neglected migration from sub-Saharan Africa despite this region’s demonstrated migration potential. This book uses a novel quantitative data source, the Migration Between Africa and Europe (MAFE) study, to examine the production of irregular legal status among Senegalese migrants in France, Italy, and Spain and the consequences of configurations of irregularity. A historical chapter outlines the evolution of immigration policies in each country that set the parameters for irregular legal status. The first empirical chapter studies the pathways into irregular status for Senegalese migrants. Pathways early in a migrant’s trip—no-visa entry and overstaying—are more sensitive to both contextual variables and access to forms of capital, indicating that both state control and migrant agency shape these pathways. In contrast, befallen irregularity is less related to contextual variation, perhaps because immigration policies and enforcement resources are not focused on migrant integration. The second empirical chapter examines how immigration policy creates gendered channels of access to labor markets. Senegalese women with configurations of legal status indicative of family reunification are more likely than women with other legal statuses to be economically inactive upon arrival, while there is little association between Senegalese men’s legal status and their participation. Results show, however, that family reunification does not preclude labor-market participation, as women with family-reunification profiles eventually transition into economic activity